The Effect of Using Self-regulated Learning Strategy on Self-Efficacy and Academic Writing Performance of College Students in Indonesia - Masrul, Masrul; Ayu, Citra (English Teaching Journal : A Journal of English Literature, Language and Education, 2023)
This study examined the correlation between self-efficacy and English academic writing performance among college students in Indonesia and assessed the effect of SRL strategy on EFL students' self-efficacy. The descriptive and correlation statistics were used to analyze the data. In this study, students were classified into three categories (high, moderate, and low) based on their rate of SRL in order to examine the relationships between SRL strategy usage, self-efficacy, and academic writing performance. The results indicated that overall SRL strategy and self-efficacy in academic writing were moderate. Students who were more frequently exposed to SRL strategies showed higher self-efficacy in academic English writing. A broader set of student characteristics could be useful in future research.